Accuracy of transient elastography in Identifying fibrosis among patients with Chronic hepatitis b: a cross-sectional Observational study - Rony, Rajib Saha; Hossain, Ahmed; Islam, Md Daharul; Karim, Md Fazal; Rahman, Aminur; Jui, Sudipta Saha (Bangladesh Journal of Medicine, 2023)
Background: Hepatitis B virus (HBV) infection is a significant global public health problem, affecting millions of people worldwide. Liver biopsy is the gold standard for assessing fibrosis but is invasive and carries post-procedural risks. Noninvasive tests to evaluate liver fibrosis are needed, and transient elastography is one such method. This cross-sectional observational study aimed to assess the accuracy of transient elastography in identifying fibrosis among patients with chronic hepatitis B. Methods: The study was conducted at the Department of Medicine and Hepatology, Sir Salimullah Medical College Mitford Hospital, Dhaka. The study subjects were patients diagnosed with chronic hepatitis B infection, both outpatient and inpatient cases. Data were collected from 25 patients using convenient and purposive sampling techniques. Demographic data, clinical examination, and relevant investigations were recorded in a structured case report form. Data were processed, registered, edited, computerized, and analyzed. Results: The study included 25 patients with a mean age of 26.8±6.5 years, predominantly male (80%). All patients were HBsAg positive, 12.0% were HBeAg positive, and 56.0% were antiHBe positive. The mean HBV DNA PCR was 1516293.4±7475976.3 IU/ml. The mean ALT level was 45.4±13.8 U/L. The mean liver stiffness measurement (LSM) was 7.5±2.3 kPa, with 64.0% of patients showing fibrosis stage F0-F1. The mean periportal +/- bridging necrosis was 2.92±1.58, intralobular degeneration and focal were 1.16±0.55, portal inflammation was 2.52±0.87, histological activity index was 6.6±2.2, and fibrosis score was 1.44±1.04. Positive correlations were observed between LSM and histological activity index (r=0.239; p=0.251) and between LSM and fibrosis score (r=0.107; p=0.612). Conclusion: Our study demonstrates that transient elastography provides a non-invasive, easy, and cost-effective method for identifying fibrosis in chronic hepatitis B patients, serving as a potential alternative to liver biopsy. Bangladesh J Medicine 2023; 34(3): 199-205